An investigation on wear properties of SiC/WC strengthened aluminium alloy hybrid composites. (2021) - Jayakanth, J.J.; Mamidi, Vamsi Krishna; Pugazhenthi, R.; Anbuchezhiyan, G.; Ponshanmugakumar, A.
Abstract: Particulates strengthened aluminium hybrid intermixtures is formed using squeeze casting method by varying weight percentage (2%, 4% and 6%) of SiC and keeping 2% WC constant. Pin on disc of wear test has been used to investigate the wear properties and coefficient of friction of synthesized aluminium hybrid composites under dry sliding conditions by varying its load and sliding speed. The sliding distance had been maintained constant. The structural features of the synthesized composites and its morphological properties were studied by Scanning Electron Microscope (SEM). Wear rate of synthesized mixtures is significantly increased at all affixed loads. SEM images of the worn out surfaces revealed that particulates micro fracture was the predominant mechanism associated with abrasive wear. Micro hardness of Aluminium hybrid been significantly increased due to incorporation of stronger and stiffer reinforced particles and it leads to low wear with high friction coefficient developed hybrid compared with monolithic material.